2011
DOI: 10.1042/cs20110299
|View full text |Cite
|
Sign up to set email alerts
|

You may need the vagus nerve to understand pathophysiology and to treat diseases

Abstract: Can different pathophysiological mechanisms and risk factors leading to various diseases be linked with altered transmission of signals by one common pathway? The present article provides evidence for the hypothesis that adequate vagal nerve activity reduces the risk of major diseases, via common basic mechanisms and interim risk factors. These diseases include cardiovascular disease, cancer, Alzheimer's disease and the metabolic syndrome. Three basic mechanisms contribute to such illnesses: local oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 45 publications
2
69
0
Order By: Relevance
“…Therefore, these findings suggest that in cancer patients, vagal function deteriorates as the tumor burden increases. De Couck et al also observed low vagal function in advanced stage compared to the early stage of cancer but involving only r-MSSD as an indicator for vagal function whereas our study involved both E:I ratio and r-MSSD [4]. Their study population included comorbid conditions such as cardiovascular disease and diabetes which are known to influence vagal function indicators whereas our study populations were only with cancer.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, these findings suggest that in cancer patients, vagal function deteriorates as the tumor burden increases. De Couck et al also observed low vagal function in advanced stage compared to the early stage of cancer but involving only r-MSSD as an indicator for vagal function whereas our study involved both E:I ratio and r-MSSD [4]. Their study population included comorbid conditions such as cardiovascular disease and diabetes which are known to influence vagal function indicators whereas our study populations were only with cancer.…”
Section: Discussionmentioning
confidence: 61%
“…ANS controls most of the viscera, and many solid cancers are formed in the same viscera [3,4]. Consequently, recent studies have revealed autonomic dysfunction in cancer patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of vagal nerve activity on clinical outcomes were hypothesized to occur as a result of the known inhibitory roles of this nerve on three mechanisms promoting tumor onset and progression (excessive inflam mation, excessive sympathetic activity and oxidative stress) (21). Vagal nerve activity was indexed by heart rate variability (HRV) obtained from a 10 sec ECG at approximately the time of cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the metastatic process is also under the control of sympathetic neurotransmitters, which influence the migratory ability of cancer cells and determine the direction and the development of metastases (16). Vagal nerve activity is inversely related to and inhibits all these three mechanisms (17)(18)(19)(20)(21). Based on converging evidence, Gidron et al (22) hypothesized that vagal nerve activity may modulate tumor growth, and if this model is valid, might become a variable that could be used as a prognostic factor and could be therapeutically manipulated.…”
Section: Introductionmentioning
confidence: 99%
“…In male patients with locally recurrent or metastatic cancer (principally lung and gastrointestinal cancer) a higher HRV is significantly associated to survival; in patients with different cancer sites, HRV appears systematically decreased; in patients with terminal hepatocellular carcinoma, HRV indices were significantly associated with Time-toDeath [48][49][50]. This influence can be understood since Vagal afferents and efferents might inhibit three mechanisms involved in cancer etiology and progression: local oxidative stress and DNA damage, inflammatory reactions and excessive sympathetic responses [51].…”
Section: Hrv and Pathology: Influences And Interventionmentioning
confidence: 99%